Modeling the Vertical Backscattering Distribution in the Percolation Zone of the Greenland Ice Sheet With SAR Tomography - Fischer, Georg; id_orcid:0 000-0002-7987-5453; Jäger, Marc; Papathanassiou, Konstantinos P.; Hajnsek, Irena (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2019)
ISSN:1939-1404 ISSN:2151-1535